Maternal protein restriction induce skeletal muscle changes without altering the MRFs MyoD and myogenin expression in offspring - Cabeço, Ludimila Canuto [UNESP]; Budri, Paulo Eduardo [UNESP]; Baroni, Mirella [UNESP]; Castan, Eduardo Paulino [UNESP]; Carani, Fernanda Regina [UNESP]; Tome de Souza, Paula Aiello [UNESP]; Boer, Patricia Aline [UNESP]; Michelin Matheus, Selma Maria [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Springer, 2012)
Stimuli during pregnancy, such as protein restriction, can affect morphophysiological parameters in the offspring with consequences in adulthood. The phenomenon known as fetal programming can cause short- and long-term changes in the skeletal muscle phenotype. We investigated the morphology and the myogenic regulatory factors (MRFs) MyoD and myogenin expression in soleus, SOL; oxidative and slow twitching and in extensor digitorum longus, EDL; glycolytic and fast twitching muscles in the offspring of dams subjected to protein restriction during pregnancy. Four groups of male Wistar offspring rats were studied. Offspring from dams fed a low-protein diet (6 % protein, LP) and normal protein diet (17 % protein, NP) were euthanized at 30 and 112 days old, and their muscles were removed and kept at -80 A degrees C. Muscles histological sections (8 mu m) were submitted to a myofibrillar adenosine triphosphatase histochemistry reaction for morphometric analysis. Gene and protein expression levels of MyoD and myogenin were determined by RT-qPCR and western blotting. The major findings observed were distinct patterns of morphological changes in SOL and EDL muscles in LP offspring at 30 and 112 days old without changes in MRFs MyoD and myogenin expression. Our results indicate that maternal protein restriction followed by normal diet after birth induced morphological changes in muscles with distinct morphofunctional characteristics over the long term, but did not alter the MRFs MyoD and myogenin expression. Further studies are necessary to better understand the mechanisms underlying the maternal protein restriction response on skeletal muscle.
Keywords: Skeletal muscle; Maternal protein restriction; Pregnancy; Fetal programming; Myogenic regulatory factors